METODOLOGI PEMAHAMAN HADIS: PENDEKATAN PEMAHAMAN TRADISIONALIS DAN MODERNIS - Budiman Nur (DIRAYAH : Jurnal Ilmu Hadis, 2023)
There are many aspects of the Hadith science study, the methodology of understanding Hadith (fiqh al-hadîts) is a dimension that is not less important after the science of dirâyah and musthalah hadith. This is because fiqh al-hadîts is a study that tries to explore and understand the teachings contained in the Hadiths of the Prophet so that they can be practiced throughout time. This ability is actually the most important in bringing out and strengthening the character of a religion that is moderate, not burdensome and shâlih li kulli zamân wa makân (always in harmony with any space and time). This re-understanding of the Hadiths of the Prophet is intended in order to maintain and defend the Hadiths as long as these Hadiths can be said to have acceptable scientific validity as something originating from the Prophet (maqbul). Understanding also aims not only to communicate with the realities of the times, but also to develop meanings as far as the Hadith editor can reach. Therefore, utilizing various methods of understanding Hadith is a positive and advanced step in re-understanding the Prophet's Hadith in the modern world, whether using traditionalist or modernist methods of understanding.